Impacts of social vulnerability on the mental health of families followed by Primary Health Care (Research, Society and Development, 2026)
This study aims to analyze, based on territorial practice, the impacts of social vulnerability on the mental health of families assisted by Primary Health Care (PHC) services and the Primeira Infância Melhor Program (PIM), relating real observations, scientific literature, and current public policies. This is a qualitative study, characterized as an experience report, developed from professional practice in the territory, with systematic records of experiences, observations, and follow-up of families in situations of social vulnerability. The results reveal the presence of chronic psychological distress, maternal overload, weakening of affective bonds, food insecurity, housing precariousness, and transgenerational cycles of vulnerability, directly impacting child development and caregivers’ mental health. It is concluded that early interventions, qualified listening, strengthening Primary Health Care, and intersectoral public policies are essential for building emotionally safe environments and reducing psychosocial harm in contexts of social vulnerability.